Do Librarians Feel that Their Profession Is Valued in Contemporary Schools?. Issue 1 (2nd January 2019) - Merga, Margaret Kristin
ABSTRACT: Teacher librarians are qualified educators, however their educational contribution many not be well known or acknowledged, and they receive scant consideration in the educational research literature. As perception of the valuing of one's profession can influence job satisfaction and morale, this study explores teacher librarians' perceptions of the valuing of their profession in contemporary schools. The teacher librarians interviewed did not typically feel secure in the knowledge that their profession is valued, identifying a range of factors that contributed to this perspective. Respondents often perceived a high level of vulnerability when comparing themselves to their classroom teacher colleagues. Staffing vulnerability, their status as educators outside the classroom, patchy teacher support, low administrator regard and understanding, and the decline of valuing of the profession over time were raised as potential issues influencing teacher librarians' morale. However, teacher librarians often sought to be more effective advocates for their role, refusing to passively accept the status quo. Findings suggest that school administrators may play a powerful role in promoting the valuing of this profession.